GAMBARAN PENGETAHUAN REMAJA PUTRI TENTANG KESEHATAN REPRODUKSI KELAS X SMAN 1 LALAN MUSI BANYUASIN - Lilik Pranata (Jurnal Akademika Baiturrahim Jambi, 2018)
Reproductive health is a state of complete physical, mental and social well-being not only free from disease or disability in all aspects related to the reproductive system, its functions and processes. Reproductive health includes: reproductive organs, adolescent sexual behavior, pregnancy, risky sexual behavior of adolescents, sexually transmitted diseases (STDs).Objective: Knowing the image of young women's knowledge about reproductive health class X SMAN 1 Lalan Musi Banyuasin.Method: Descriptive quantitative by using Cross Sectional design done with interview technique with questioner to 60 respondents with purposive sampling technique.Results: Knowledge of reproduction tools, 34 respondents (56.7%) had enough knowledge and 11 respondents (18.3%) had good knowledge. Knowledge of adolescent sexual behavior, 25 respondents (41,6) have enough knowledge and 16 respondents (26,7%) have good knowledge. Knowledge of pregnancy, 33 respondents (55%) have enough knowledge and 5 respondents (8.3%) have good knowledge. Knowledge about risky sexual behavior, 25 respondents (42%) have less knowledge and 13 respondents (21.6%) have good knowledge. Knowledge of sexually transmitted diseases (STDs), 35 respondents (58.3%) had less knowledge and 7 respondents (11.7%) had good knowledge. Improving adolescent knowledge should be carried out for health counseling to schools, as well as providing additional materials on reproductive health and using UKS facilities to the maximum extent possible.